A COMUNICAÇÃO ORGANIZACIONAL INTERNA E O AMBIENTE VIRTUAL: NOVAS TENDÊNCIAS - Sanchez, Lúcia Helena Aponi (2006)
This thesis deals with the impact of the virtuality on the internal communications of the organizations and aims to analyze and describe the changes in internal communications of private organizations due the rise of new technologies. In order to achieve our goal we have reviewed the relevant bibliography ranging from communicational theories to technical resources of the information technology applied to the organization. We also established what tendencies and effects can be observed by a qualitative study with experts in communicational area, using the Delphy Panel method, aiming to describe and analyze the changes in media, their impacts, and trace a possible landscape regarding the uses of information technology and the communication in internal organizational environment. The results showed that the internal organizational communication has to be sorely computer mediated, but not limited to it, as each cultural and organizational reality will defines its own communicational mix a set of traditional and virtual medias which has to be the most logical conjunction of channels to achieve an effective communication, since the organization demands a wide range of message formats in order to fulfill the needs of their publics.